2020
DOI: 10.1080/1047840x.2020.1820225
|View full text |Cite
|
Sign up to set email alerts
|

Young People’s Digital Interactions from a Narrative Identity Perspective: Implications for Mental Health and Wellbeing

Abstract: The current response article began by situating this journal volume in the current COVID-19 pandemic context which has driven young people into digital spaces for far longer periods of time than ever. Many scholars, policy makers, and the public at large are recognizing that these social digital spaces may be the only outlet by which youth and their families can remain safe (at least physically), while also participating in some important social outlets. We discussed the notion of hybrid reality and argued tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 97 publications
0
2
0
3
Order By: Relevance
“…Other research shows that in 2017 and 2018, a large share of 13‐ and 15‐year‐old European adolescents reported that they were interacting online with friends and others almost all the time throughout the day (36% and 41%, respectively; Inchley et al, 2020 ). From a developmental perspective, it is understandable why social media are so popular among early and middle adolescents (Granic et al, 2020 ). Social media allow young adolescents to form and maintain peer relationships (e.g., through instant messaging), to share their perspectives, narratives, and self‐portrayals with others (e.g., by uploading personal photos, videos, and texts), to receive feedback on their appearances and online behaviors (e.g., through “likes” and responses from peers), and to learn from others (e.g., by browsing through peers’ uploads).…”
mentioning
confidence: 99%
“…Other research shows that in 2017 and 2018, a large share of 13‐ and 15‐year‐old European adolescents reported that they were interacting online with friends and others almost all the time throughout the day (36% and 41%, respectively; Inchley et al, 2020 ). From a developmental perspective, it is understandable why social media are so popular among early and middle adolescents (Granic et al, 2020 ). Social media allow young adolescents to form and maintain peer relationships (e.g., through instant messaging), to share their perspectives, narratives, and self‐portrayals with others (e.g., by uploading personal photos, videos, and texts), to receive feedback on their appearances and online behaviors (e.g., through “likes” and responses from peers), and to learn from others (e.g., by browsing through peers’ uploads).…”
mentioning
confidence: 99%
“…Com o contexto da pandemia de COVID-19, as interações nos espaços digitais tiveram aumento na frequência e intensidade. As mídias sociais e jogos se configuraram como uma das maneiras de distração, bem como para manter os jovens e suas famílias seguras, em isolamento social, facilitando a comunicação (Granic, Morita, & Scholten, 2020). Alguns estudos apontam que cerca de 20% dos adolescentes americanos permanecem mais de dez horas no acesso às telas, fato que pode estar relacionado com o aumento nas doenças psiquiátricas e internações de adolescentes (Mojtabai, Olfson, & Han, 2016).…”
Section: Resultsunclassified
“…Os dispositivos digitais são uma fonte valiosa de apoio social e extremamente necessários para desenvolver habilidades para as economias no futuro (Odgers, & Jensen, 2020). O uso da internet pode resultar em comportamentos de dependência, mas também oferece recursos criativos, experiências pessoais e sociais que proporcionam gratificações (Dhir et al, 2015), oferecendo intervenções para a promoção da saúde mental e bem-estar (Granic, Morita, & Scholten, 2020). Há relatos de utilidade da mídia social na prevenção do suicídio, permitindo um fórum para o compartilhamento de experiências sem julgamentos (Robinson et al, 2016).…”
Section: Diante Do Aumento Do Envolvimento Dos Adolescentes Com Internet O Transtorno Do Jogo Foi Incluído No Manualunclassified
“…Applying this to digital media usage, it is to be expected that users who engage in downward comparison (i.e., viewing the current self as better than the past self when comparing recent online photos with the earlier photos) may experience increases in their mental health. Although it remains to be seen, the effects of downward comparison may be of even greater significance for adolescent digital media users who are undergoing the task of developing a personal fable (Elkind, 1967;Erikson, 1959;Granic et al, 2020aGranic et al, , 2020b.…”
Section: Consider a Variety Of Mechanisms And User Variables As Media...mentioning
confidence: 99%